Amplified CO2 reduction of greenhouse gas emissions with C2CNT carbon nanotube composites. (December 2019) - Licht, S.; Liu, X.; Licht, G.; Wang, X.; Swesi, A.; Chan, Y.
Abstract: Production of cement, aluminum, magnesium, titanium, and steel structural materials generate more than 2 gigatonnes of CO2 globally per year. Replacement of structural materials with lightweight, stronger carbon nanotube (CNT) composites reduces the structural material's production aggregate requirements by achieving the same strength with less material. This averts a massive CO2 emission in the production of structural materials. CNTs have the highest measured tensile strength of all materials and form strong composites, but until recently, they were produced only by high carbon footprint processes. CNTs are synthesized in this study from CO2 (are carbon negative) by low-energy C2CNT (CO2 to CNT) molten electrolysis. Four tonnes of CO2 electrolyzed forms one tonne of CNTs. This avoids several hundred tonnes of CO2 by replacing structural materials with CNT composites. For example, a 2-tonne cement block with 0.001 tonne of CNTs has the same strength as a 3-tonne block without CNTs. The 1-tonne cement avoided eliminates its CO2 production emission. Specifically, a 0.048 wt% CNT-cement composite eliminates 840 tonne of CO2 /tonne CNT. CO2 is eliminated from the anthropogenic carbon cycle at less than 1 per tonne. High carbon footprint materials such as aluminum trigger larger CO2 composite elimination effects, and 1 tonne of CNT extraordinarily eliminates more than 4000 tonne CO2 /tonne CNTs.